2001
DOI: 10.1046/j.1463-1326.2001.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a combination of herbs on appetite suppression and weight loss in rats

Abstract: Data collected on rats suggest that the herbal formulation examined might be a useful and safe combination to overcome the overweight state and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In previous reports, an herb or mixture can bring unexpected actions, because of interactions among ingredients [33,34] . Talpur et al [34] had evaluated the ability of a Chinese herbal formulation previously associated with weight loss to infl uence appetite and weight loss in a carefully controlled laboratory study performed on rats. There was no greater change in weight loss or food intake with the higher dose of the herbs compared to the low dose, on the contrary, the weight loss was greater in the low dose.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, an herb or mixture can bring unexpected actions, because of interactions among ingredients [33,34] . Talpur et al [34] had evaluated the ability of a Chinese herbal formulation previously associated with weight loss to infl uence appetite and weight loss in a carefully controlled laboratory study performed on rats. There was no greater change in weight loss or food intake with the higher dose of the herbs compared to the low dose, on the contrary, the weight loss was greater in the low dose.…”
Section: Discussionmentioning
confidence: 99%
“…We expected that the reductive effects of triglyceride and LDL cholesterol would be dose dependent, but the results did not show a dose-dependent manner. It may be caused by metabolic changes that are likely to happen in animal experiments [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Bofutsusho-san formula has been shown to prevent intimal thickening and vascular smooth muscle cell proliferation in rats [ 14 ]. Furthermore, an in vivo study demonstrated that a Chinese herbal formula significantly reduced the weight of overweight rats and suppressed their appetites [ 15 ]. A herbal treatment, known as 9D-ASR also leads to a decrease in the weight of overweight rats [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%